Medijski aspekt nastanka i razvoja međukulturalne komunikacije / The Media Aspect of Intercultural Communication's Origin and Development (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
With the emergence of new means of communication and transportation, intercultural communication transformed its properties into a new context called new media. Arguably, many scholars asserted how this new form of media has accelerated the globalization process, and through this it would inevitably lead cultural homogenization. Alan Dershowitz famous statement “Internet knows no borders“ came to realizing itself. Especially with the social media national borders are overcame by individuals, and distant communication is made possible. Two people from distant countries with distinct cultures are now able to share a habitat of meaning. Intercultural communication can be best explored through media context, because media is the one without which this phenomenon would neither appear nor function.
Keywords: media; culture; intercultural communication; globalization; factors and impacts on society